2018
DOI: 10.19171/uefad.450103
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Inquiry Based Learning Approach For Students’ Academic Success In Science Teaching

Abstract: Araştırmadaki nicel ve nitel verilerin birbirini desteklediği, ön test ve son test puanları arasındaki farkın yüksek olduğu tespit edilmiştir. Nitel verilerin analizleri sonucunda; öğrencilerin derse karşı ilgilerinin arttığı, el becerilerinin geliştiği, deneyerek daha iyi öğrendikleri, merak duygularının arttığı, eğlenerek öğrendikleri ve derse daha etkin biçimde katıldıkları sonucuna varılmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In the literature, it was reported that an inquiry-based learning approach increases students' interest in the course (Bilir, 2015), provides effective learning (Alouf & Bentley, 2003;Bozkurt, 2012;Bozkurt et al, 2013, Cuevas et al, 2005Çelik & Deaktor, 2005Çelik & Deaktor, , Çavaş, 2012Wu & Hsieh, 2006) and increases students' participation in the course (Bilir, 2015;Coşkun, 2018;Lin et al, 2009). It has also been determined that the Layered Inquiry-Based Learning Model provides order in the learning process to be developed differently from the other studies.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, it was reported that an inquiry-based learning approach increases students' interest in the course (Bilir, 2015), provides effective learning (Alouf & Bentley, 2003;Bozkurt, 2012;Bozkurt et al, 2013, Cuevas et al, 2005Çelik & Deaktor, 2005Çelik & Deaktor, , Çavaş, 2012Wu & Hsieh, 2006) and increases students' participation in the course (Bilir, 2015;Coşkun, 2018;Lin et al, 2009). It has also been determined that the Layered Inquiry-Based Learning Model provides order in the learning process to be developed differently from the other studies.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, as a result of this study, it can be said that the method of learning arguments-driven inquirys parallels the views expressed by students about the development of skills such as communication and decision-making in themselves with literature. In this context, studies have been found that research-inquiry-based learning improves problem-solving skills, in-depth thinking, conceptual understanding and creativity in students (Bilir & Özkan, 2018;Bliss & et al, 2007;Duban, 2008;Yasar & Duban, 2009;Wu & Hsieh, 2006;Wallace & Kang, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the study of the relevant literature, studies have been found that argumentation-based learning and research query-based learning methods improve the affective characteristics of students (Bliss & et al, 2007;Blumenfeld & et al, 1991;Can, 2012;Calıskan, 2008;Eilam, 2002;Genctürk & Türkmen, 2007;Lord & Orkwiszewski, 2006;Polman, 2000;Sen, Yilmaz & Erdogan, 2016;Taskoyan, 2008;Tatar, 2012;Tuan, Chin, Tsai & Cheng, 2005 laboratories responsibilities of the students by learning more in the course of participation, the learning process is more effective, the students develop their ability to ask better questions and to ask questions on the subject are more motivated, self-confidence and an improved ability to reported that there is an increase in the scientific process. As a result of the Bilir (2015) study, the research stated that students learned by having fun and effectively in the sense of learning, learned based on experimentation and observation, learned that their knowledge is permanent and participated effectively in the lesson; motivation in the affective sense and positive attitude towards the lesson, learned by doing group work in the sense of social impact. At the same time, as a result of this study, it can be said that the method of learning arguments-driven inquirys parallels the views expressed by students about the development of skills such as communication and decision-making in themselves with literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations